Bilateral facial nerve palsy secondary to an atypical presentation of Gullain-Barré syndrome - Mohd Shah, Azarisman Shah; Che Abdullah, Shahrin Tarmizi; Omar, Ahmad Marzuki; Nik Ahmad, Nik Nur Fatnoon; Rathor, Mohammad Yousuf (Kulliyyah of Medicine, International Islamic University Malaysia, 2009)
Bilateral simultaneous facial nerve palsy is an extremely rare clinical entity and may occur in association with a variety of neurological, infectious, neoplastic or degenerative disorders. We describe a patient, who presented with facial diplegia and normal reflexes on examination. During the entire hospitalization, he developed no motor weakness and remained ambulatory. Whether treatment is warranted for this and other milder variants of Gullain-Barré syndrome is also discussed. Atypical presentations with preserved or brisk reflexes, can be a diagnostic dilemma.